CONSUMER PROTECTION LAWS IN COMMERCIAL TRANSACTIONS: EVALUATING THE CRUCIAL SIGNIFICANCE CONSUMER-CENTRIC COMMERCE REGULATIONS IN INDONESIA - Widiarty, Wiwik Sri; Jian, Zang Huai (Jurnal Pembaharuan Hukum, 2023)
In the context of daily commercial transactions within Indonesian society, the inherent activity of commercial transaction is omnipresent. This economic exchange predominantly involves two primary actors: the seller, functioning as a business entity, and the buyer, embodying the consumer role. Despite the ubiquity of such transactions, the imbalance in potential losses, particularly on the part of consumers, underscores a pressing concern. In response, Indonesia has instituted consumer protection laws to safeguard the rights of consumers. Nevertheless, a substantial knowledge gap persists among the populace regarding the critical significance of these legal provisions in the commercial transaction milieu. To bridge this awareness deficit, the researcher embarked on an inquiry aimed at elucidating the indispensable nature of consumer protection laws for both sellers operating as business entities and buyers assuming the consumer role. This article delves into the essence of commercial transaction, explicates the underpinnings of consumer protection laws, and articulates their pivotal role for sellers and buyers alike. By employing a descriptive methodology, this research illuminates pertinent concepts and conducts analyses to underscore the indispensability of consumer protection laws from both vantage points. The findings underscore that consumer protection laws are integral to the integrity of commercial transaction.